Lateral Bearing Characteristics of Bucket Foundation Breakwaters in Soft Soil of Port Areas - WANG Shuai, ZHANG Jia-lin, HU Shao-wei, YOU Jian-hua, YANG Yu-ming (长江科学院院报)
[Objectives] This study aims to investigate the lateral bearing characteristics of bucket foundation breakwaters, focusing on their failure modes, ultimate bearing capacity, the relationship between rotation and displacement, soil-structure interaction, and cyclic bearing behaviors. The goal is to improve computational theories of bucket foundation breakwaters and support their engineering design and applications. [Methods] Based on the actual structural configurations, a 1∶20 large-scale test model was designed, along with a foundation bed model simulating the sandy soil conditions of port areas, to simulate the service performance of bucket foundation breakwaters. The loading process covered the entire phase from post-installation to failure. While validating the test conditions using the finite element analysis, supplementary finite element analysis was conducted for different structural configurations and soil conditions, enabling a systematic study of the bearing characteristics and load response of bucket foundation breakwaters. [Results] (1) In the early stage of installation, the sidewall friction increased linearly, with the average friction measured in the test being 41.23 kPa and the average friction coefficient 0.405. (2) The failure mode was general shear failure. The displacement pattern at the limit state obtained from numerical analysis was consistent with the test results. When the displacement reached 150.3 mm, the maximum displacement of the soil on the rear side was 54.2 mm. (3) The ultimate bearing capacity obtained from the model test was 14.26 kN, while the finite element analysis calculated 15.07 kN, with a relative error of 5.68%. The deformation process of bucket foundation breakwaters could be divided into three stages: quasi-elastic stage, plastic stage, and failure stage. In the quasi-elastic stage, the displacement increased linearly, with an elastic limit displacement of about 1.0%L and a plastic limit displacement of about 3.0%L. (4) Before failure, earth pressure in the passive zone increased with displacement, reaching a maximum increment of 74.2 kPa. Earth pressure in the active zone was significantly smaller, with a maximum increment of 10.2 kPa. The variation trends of earth pressure on the connecting wall and the cylinder wall were consistent, and the deformation coordination between the foundation and the internal soil was relatively good. (5) The bearing capacity of bucket foundation breakwaters in sandy soil was better than in silty clay, which was better than in silt. Under the same displacement, rotation was more pronounced in sandy soil, while under identical loading conditions, the most significant rotation occurred in silt. (6) The ultimate bearing capacity of the bucket foundation breakwaters was negatively correlated with both the length-to-height ratio and width-to-height ratio, but positively correlated with the length-to-height ratio. (7) Under lateral cyclic loading, the bucket foundation breakwaters showed cyclic hardening during positive rotation and cyclic degradation during negative rotation. The stiffness reduction was more pronounced during positive rotation. [Conclusions] The deformation of bucket foundation breakwaters has three stages: quasi-elastic, plastic, and failure stages. The overall failure mode is general shear failure, and there is a high degree of deformation coordination between the foundation and the soil. Soil type significantly affects bearing capacity, with sandy soil performing the best and silt the worst. In addition, the geometry layout greatly influences performance. Under cyclic loading conditions, the bucket foundation breakwaters exhibit enhanced plastic deformation capacity, good energy dissipation, and excellent seismic performance.